A framework for technology adoption for a virtual university - Gogan, Nadium Achieng (Strathmore University, 2013)
Virtual universities have emerged as a viable option for accessing university education due to the rapid advancement of Information, Communication and Technology (ICT) particularly internet based. This has become more relevant considering the increased demand for higher education and the need to provide equal opportunity by the policy-makers. However, most Kenyan universities are hesitant to establish VUs due to the huge cost of establishing and costs of maintaining the system, according to Kariuki (2006) Kenyan universities are a distant away from reaping the benefits of distant education. Research has shown that for successful implementation of the Virtual University, there is need for a framework that will inform the design, development, delivery and evaluation of flexible, open and distance learning environments. The framework will outline the critical success factors for an e-leaming environment such as those identified by Khan (2005): pedagogical, technological, interface design, evaluation, resource support, ethical, management and institutional. Considering that Kenyan Universities have been implementing the Virtual Universities, they have based their decisions on European and American markets research on critical success and failure factors that have a totally different socio-cultural and economic background. There is need for a framework that takes cognizance of the local context to be developed that will guide the implementation of the Virtual University. This study focused on the Virtual Universities implementation in Kenya and seeks to establish the Critical Success Factors and Challenges that have so far been experienced. It focused on the three Universities namely Kenyatta University, Mount Kenya University and Inoorero University that have managed implement it for relatively longer period compared to other universities in the country. From the study it revealed that the virtual university is more suited for theoretical courses and it prevents a huge challenge when introducing a new course that will require simulations and practicals. Most universities noted that for successful implementation of virtual university suitable courses should be introduced with requisite reference materials for course outline and continuous evaluation of the program to ascertain its effectiveness. It should also have a buy-in from faculty or institutional management. The study shows that though most of the instructors have adequate training, technology keeps on changing and there is need for them to keep abreast. This means refresher courses should be conducted for those already trained. It is equally important to ensure that online assessments and assignments are conducted properly in order to safeguard the credibility of the VUs and avoid any unethical behavior from the students. The study eventually recommends a framework for successful implementation of Virtual Universities based on the findings of the research.
A Kenyan perspective
A Project Thesis Submitted in Partial Fulfillment of Masters of Science in Information Technology
Keywords: Framework; Adoption; Virtual; University; Kenyan